Empowerment of health cadres through digital education to enhance knowledge, attitudes, self-efficacy, and behavior of exclusive breastfeeding mothers - Mintarsih, Sri; Mulyani, Sri; Andayani, Tri Rejeki; Sumardiyono, Sumardiyono; Ulfaviani, Anisa Laksita (Edelweiss Applied Science and Technology, 2025)
Digital transformation is needed for mothers to utilize the importance of exclusive breastfeeding by empowering the role of cadres in it. This study aims to examine the effectiveness of empowering health cadres through digital education using website-based digital education media called Halo_ASIEK to improve the knowledge, attitudes, self-efficacy, and behaviors of exclusive breastfeeding mothers through ADDIE Model (Analyze, Development, Design, Implementation and Evaluation). ADDIE Model is necessary to conduct a product development analysis so that it can reach the intended purpose. The education were delivered by the health cadres to mothers with Trainers on Trainers (TOT) approach. Based on the analysis carried above, the digital education was needed. The quantitative data analysis on the knowledge showed that there is an improvement. The mother's attitude also became more positive, with a significance of 0.000 (<0.05). Based on univariate analysis, it was also found that there was a change in the mother's self-efficacy regarding her ability to provide exclusive breastfeeding, it is increased by 45.5% with a significance of 0.000 (<0.05). It was also found that digital education has a significant effect on the mother's behaviours with significance (0.000 <0.05). It can be concluded that digital education has significant positive impacts on knowledges, attitudes, self efficacy and behaviours on breastfeeding mothers.